The Role of Oil Phase in the Stability and Physicochemical Properties of Oil‐in‐Water Emulsions in the Presence of Gum Tragacanth. (17th June 2019) - Abdolmaleki, Khadije; Mohammadifar, Mohammad Amin; Sheikhi, Zhian; Matinfar, Golshan; Nayebzadeh, Kooshan
Abstract: Different emulsions based on six types of vegetable oils (sunflower, canola, sesame, olive, coconut, and palm olein) were studied to investigate the role of the oil phase in the stability and physicochemical characteristics of oil‐in‐water emulsions prepared with gum tragacanth. The results indicated that the stability, rheological parameters, and size distribution of emulsions were dependent on the oil type. Based on the interfacial tension value, the type of oil did not have a significant effect on the gum tragacanth‐emulsifying properties. The formulation based on sunflower and coconut oil led to producing more stable emulsion and a sample containing palm olein resulted in an unstable emulsion. Rheological analysis revealed that the sample based on palm olein showed the lowest consistency coefficient (2.10 ± 0.05 Pas n ), elastic modulus (3.90 ± 0.21 Pa), and energy of cohesion (80.87 ± 1.1 J m −3 ). This study revealed that using oils with lower viscosity and higher density led to the higher stability of the emulsion samples.